2013
DOI: 10.1002/jid.2924
|View full text |Cite
|
Sign up to set email alerts
|

An Island Drifting Apart. Why Haiti Is Mired in Poverty While the Dominican Republic Forges Ahead

Abstract: The 2010 earthquake in Haiti has exposed the extreme vulnerability of a society where the state and the economy simultaneously fail to deliver. The Dominican Republic has witnessed several phases of rapid economic growth since the 1870s and, from the 1970s onwards, a sustained process of political emancipation. Douglas North, John Wallis and Barry Weingast have developed a conceptual framework to explain different long-term performance characteristics of societies, which we apply to the case of Hispaniola. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This can then help identify the consequences of particular choices for climate-related vulnerability, establish who were the winners and losers, and reveal how such successes and failures arose. This reasoning has its pitfalls (Endfield, 2012); however, research in historical disaster studies has shown how decisions even centuries in the past can become difficult to shift and lead to the development of particular pathways that influence vulnerability and responses right through to the present (Frankema and Masé, 2014;Libecap, 2011;Rohland, 2014bRohland, , 2017Rohland, , 2018.…”
Section: Institutional Path Dependency and Memorymentioning
confidence: 99%
“…This can then help identify the consequences of particular choices for climate-related vulnerability, establish who were the winners and losers, and reveal how such successes and failures arose. This reasoning has its pitfalls (Endfield, 2012); however, research in historical disaster studies has shown how decisions even centuries in the past can become difficult to shift and lead to the development of particular pathways that influence vulnerability and responses right through to the present (Frankema and Masé, 2014;Libecap, 2011;Rohland, 2014bRohland, , 2017Rohland, , 2018.…”
Section: Institutional Path Dependency and Memorymentioning
confidence: 99%
“…Haiti remains the only successful example of a slave revolt resulting in national independence—this success came at a relatively high price in destruction of people and property, limited access to international markets, and reparations (that lasted about 100 years) transmitted to France. With independence, Haitians quickly transformed their economy from plantation to small‐scale staple agriculture (Frankema & Masé, ).…”
Section: Introduction and Haitian Contextmentioning
confidence: 99%
“…Domingue had been populated with just one goal: to produce crops for export," the order continued to "haunt" independent Haiti (Dubois, 2012, p. 8). However, there were key differences between the northern kingdom and the southern republic -which emerged after an uprising against Dessalines by leaders who included Alexandre Pétion (the eventual leader of the South) and Henry Christophe (who would lead the North) -with regard to the question of how to manage the economy (Frankema & Masé, 2014;Dubois, 2012). Nevertheless, post-independent leaders continuously remained committed to reinvigorating the plantation system, which had enormous political consequences (Dubois, 2012).…”
Section: History Of External Involvementmentioning
confidence: 99%
“…The US had a number of motives for occupying Haiti. In a highly unstable political context, the US described itself as seeking to restore political order, but their motives were also to prevent German control of the island and to gain control over a coveted port (Dubois, 2012;Frankema & Masé, 2014). Moreover, there were economic motivations at play as the US sought to establish a trusteeship that could produce free markets and free trade (Shah, 2009).…”
Section: History Of External Involvementmentioning
confidence: 99%
See 1 more Smart Citation